Analisis Pengaruh Economic Risk dan Country Risk terhadap Fluktuasi Foreign Direct Investment di Indonesia Tahun 2000-2018 - Nur Laili Ramadani; Any Widayatsari; Ando Fahda Aulia (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
This research aims to determine the effect of economic risk includes Bank Indonesia interest rate and exchange rate, and country risk on foreign direct investment in Indonesia. The method used is descriptive quantitative analyzed simultaneously and partially with OLS (Ordinary Least Square) of multiple linear regression. The result shows that simultaneously, BI rate, exchange rate and country risk has a significant effect on foreign direct investment. Meanwhile, partially, BI rate and country risk has a significant negative effect on foreign direct investment, however exchange rate has a significant positive effect on foreign direct investmen